Factors associated with relapse of schizophrenia (Bangladesh Journal of Psychiatry, 2018)
Schizophrenia is a chronic psychiatric illness with high rate of relapse which is commonly associated with noncompliance of medicine, as well as stress and high expressed emotions. The objective of the study was to determine the factors of relapse among the schizophrenic patients attending in outpatient departments of three tertiary level psychiatric facilities in Bangladesh. This was a cross sectional study conducted from July, 2001 to June, 2002. Two hundred patients including both relapse and nonrelapse cases of schizophrenia and their key relatives were included by purposive sampling. The results showed no statistically significant difference in terms of relapse with age, sex, religion, residence, occupation and level of education (p>0.05), but statistically significant difference was found with marital status and economic status (p